2020
DOI: 10.23923/rpye2020.01.182
|View full text |Cite
|
Sign up to set email alerts
|

Predictores de ser víctima de acoso escolar en Educación Primaria: una revisión sistemática

Abstract: El acoso escolar conlleva importantes consecuencias negativas para las víctimas. Por ello, es fundamental desarrollar medidas para su prevención o, en su caso, detección temprana. Para ello es imprescindible identificar sus principales factores de riesgo o protección, a partir de la evidencia científica disponible. El presente trabajo tiene como objetivo identificar los principales predictores de ser víctima de acoso escolar en Educación Primaria, a partir de una revisión sistemática de los artículos empíricos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
5
18
1
5
Order By: Relevance
“…The traditional bullying victimization instruments and criteria in our study were equivalent to those of Romera et al, so the differences can possibly be explained by a greater victimization in our study in 3rd and 4th grades compared to 5th and 6th grades. Hence, our data point to a decrease in traditional bullying throughout primary school in both sexes, in line with other studies [8,11,14], and higher rates than in secondary school. Thus, our hypothesis about a decrease of victimization rates according to age has been supported.…”
Section: Victimization In Traditional Bullyingsupporting
confidence: 93%
See 1 more Smart Citation
“…The traditional bullying victimization instruments and criteria in our study were equivalent to those of Romera et al, so the differences can possibly be explained by a greater victimization in our study in 3rd and 4th grades compared to 5th and 6th grades. Hence, our data point to a decrease in traditional bullying throughout primary school in both sexes, in line with other studies [8,11,14], and higher rates than in secondary school. Thus, our hypothesis about a decrease of victimization rates according to age has been supported.…”
Section: Victimization In Traditional Bullyingsupporting
confidence: 93%
“…Regarding sex differences, we found a higher victimization in traditional bullying in boys than in girls (except in 6th grade), similarly to other studies [8,14,16,34], placing the differences already from 3rd grade. Hence, although these data support our hypothesis of greater victimization in boys than in girls, this is not the case in 6th grade.…”
Section: Victimization In Traditional Bullyingsupporting
confidence: 90%
“…En el presente trabajo nos centraremos específicamente en la ansiedad social y la autoestima. Con respecto a la ansiedad social, existe un cuerpo de evidencia sólido acerca de su relación positiva con la victimización tradicional entre iguales en la adolescencia (Gómez-Ortiz et al, 2017;Pontillo et al, 2019;Romera et al, 2016;Suárez-García et al, 2020). Algunos estudios concluyen que la ansiedad social aumenta la probabilidad de ser víctima (Acquah et al, 2016;Pabian, & Vandebosch, 2016); y otros que ser víctima aumenta la probabilidad de tener ansiedad social (Calvete et al, 2018;Silberg et al, 2016;Van-den-Eijnden et al, 2014).…”
Section: Introductionunclassified
“…Due to the high prevalence and the impact it may have on people's lives, it is important to study the protective and risk factors associated with bullying. Some systematic reviews and meta-analyses have concluded that certain individual, family, school and community factors are related to the involvement that a person may have in bullying situations [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%